THU0480 Candidate Gene Discovery in Autoimmunity by Using Extreme Phenotypes and Whole Exome Capture. (10th June 2014) - Arcos-Burgos, M.; Johar, A.; Amaya-Amaya, J.; Mantilla, R.D.; Andrews, D.; Rojas-Villarraga, A.; Anaya, J.-M.
Abstract : Background: The multiple autoimmune syndrome (MAS) is defined as a condition characterized by the presence of three or more autoimmune diseases (ADs) in one patient. We demonstrated that MAS identifies extreme forms of ADs and is frequently clustered in families. MAS phenotypes present in families often displays Mendelian segregation ratios, representing crucial evidence for identifying major genes associated with autoimmunity. Objectives: To finds new autoimmune genes. Methods: We applied whole exome capture (WEC) and next generation sequencing (NGS) to 12 MAS sporadic cases and 24 individuals ascertained from pedigrees segregating MAS. WEC was performed using the Nimblegen kit and NGS was performed using the Illumina HiSeq platform. Our variant calling pipeline generated 22, 000 - 23, 000 variants per individual. To filter these variants, we devised appropriate strategies including minor allele frequency (MAF) in the dbSNP database, implementation effect predictor tools (PolyPhen and Sift, among others) and genes inherited as potential compound heterozygotes, and homozygotes in individuals. Results: In total we found several genes with variants that had the following characteristics: inherited in patients as a compound heterozygous or homozygous form and creating deleterious amino acid substitutions. In addition these mutations were either novel (not annotated in dbSNP) or rare (MAF less than 5%). We then implemented the Kernel Based Adaptive Cluster (KBAC) to collectively weight rare variants at candidate loci and determined which multi locus genotypes in patients were significantly enriched in cases over controls. This information was compared with data from our initial variant filtration strategies as well as pathway and network analysis tools from the Metacore Software Suite. In summary, we obtained several candidate genes with multi site variant genotypes that were substantially prevalent in autoimmune patients compared to unaffected individuals. These genes include PKD1, ALPK2 and OBSCN. Two of the 3 aforementioned genes are involved in important immunological processes such as calcium signalling, T cell activation, and immunoglobulin domain phosphorylation. Conclusions: These results suggest that these genes might be important themes for deeper studies in larger cohort of patients affected by autoimmune disorders and polyautoimmunity. Acknowledgements: Financed by Colciencias (122254531722), Bogota, Colombia. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4809